2009
DOI: 10.1086/596781
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Ertapenem Use on the Susceptibility of Pseudomonas aeruginosa to Imipenem A Hospital Case Study

Abstract: We sought to evaluate the indirect impact of ertapenem use for the treatment of extended-spectrum beta-lactamase-producing Enterobacteriaceae infections in our hospital on the susceptibility of Pseudomonas aeruginosa to imipenem. The use of ertapenem was mandated for treatment of extended-spectrum beta-lactamase-producing Enterobacteriaceae infections in the absence of nonfermenting gram-negative bacilli for 1 year. The use of imipenem was restricted. Imipenem consumption decreased 64.5%. Ertapenem consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 8 publications
0
23
2
Order By: Relevance
“…(6,7,11). In these programs, the authors concluded that the improved susceptibilities were related to decreased group 2 carbapenem use.…”
Section: Fig 2 Use Of Antipseudomonal Drugs Over the 10-year Study mentioning
confidence: 99%
See 1 more Smart Citation
“…(6,7,11). In these programs, the authors concluded that the improved susceptibilities were related to decreased group 2 carbapenem use.…”
Section: Fig 2 Use Of Antipseudomonal Drugs Over the 10-year Study mentioning
confidence: 99%
“…Previous reports have described no change in or improved susceptibility of Pseudomonas aeruginosa to carbapenems following programs of replacing group 2 carbapenems with ertapenem in the hospital setting (6,7,11). We examined the effect of the addition of ertapenem to our hospital formulary on the susceptibilities of nosocomial isolates of Enterobacteriaceae, Pseudomonas aeruginosa, and Acinetobacter baumannii to group 2 carbapenems.…”
mentioning
confidence: 99%
“…Imipenem resistance, for example, has been linked to the use of amikacin, ciprofl oxacin, and ceftazidime, but not to ertapenem. 9,11 Implementation of interventions such as the one we describe here can have a positive impact on antimicrobial resistance, because inappropriate antibiotic use is a main driver of resistance. 15 Goldstein et al reported that adding ertapenem to the formulary in a 344-bed community hospital was an effective antimicrobial management tool.…”
Section: Discussionmentioning
confidence: 99%
“…2,12,16 The premise that ertapenem has minimal activity against P. aeruginosa and is thus less likely to select for resistance has been substantiated in vitro and in clinical settings. 4,6,10,11 Still, the question of the long-term impact of ertapenem on hospital ecology lingers as overall concerns about antibiotic resistance become more pervasive.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple single-centre and multicentre ecological studies have recently been conducted that explore whether ertapenem has an impact on hospital ecology [6][7][8][9][10][11][12][13][14][15][16]. Sufficient long-term data are now available to examine whether ertapenem use has resulted in a change in the proportion of carbapenem-susceptible Pseudomonas or in other associated changes in susceptibility to carbapenems.…”
Section: Introductionmentioning
confidence: 99%